Critical financial analysis of Islamic bank in the Philippines: case study of Amanah Islamic bank - Ibrahim, Hasmiene Diocolano; Omar, Normah; Hamdan, Hamdino (Kolej University Islam Sultan Azlan Shah, 2018)
The inspiration to delve into the contemporary status of Islamic banking and finance in the Philippines has led this study to analyze the financial condition of Amanah Islamic Bank (AIB) and recommend improvements in its financial performance. This secondary databased study utilizes library research and content analysis, particularly using the capital, asset, management, earnings, and liquidity parameters. AIB is the rebranded version of Al-Amanah Islamic Investment Bank of the Philippines. At present, AIB has nine branches and is the only authorized bank in the Philippines to offer Islamic banking products and services. Presidential Decree No. 542, which was signed in 1974, directed the AIB to implement an Islamic model of banking and financing, particularly following the "no interest principle" and partnership mechanisms. However, this order was not completely implemented because "conventional banking" dominated the AIB's operation. This study contributes to the continuing effort to convert AIB into a full-fledged Islamic bank and simultaneously contend with the emerging growth of the banking industry. © 2018, Kolej University Islam Sultan Azlan Shah.